Experimental research on development of the controllable disturbances in the wake at supersonic flow around the plate - Lysenko, V.I.; Kosinov, A.D.; Yermolaev, Yu.G. (Archives of Mechanics, 2003)
The development of the artificial disturbances in the boundary layer on the flat part of a plate, the boundary layer on the opposite wedge (model stern) behind a fan of expansion waves and the wake was investigated at Mach number 2.